Protection of telecommunication network from natural hazards of global warming - Anakhov, Pavlo; Zhebka, Viktoriia; Grynkevych, Ganna; Makarenko, Anatolii (Eastern-European Journal of Enterprise Technologies, 2020)
Recently, the number of natural disasters caused by climate change on Earth has been growing in the world. To develop measures to protect hardware resources from the effects of natural disasters, the project method was used. The method developed in accordance with its provisions includes the phased collection of information on the impact of natural disasters on resources, their analysis and the development of appropriate countermeasures. The actions and manifestations of the damaging factors that were not included in the families of the corresponding damaging factors of the list "The nature of the actions and manifestations of the damaging factors of natural emergencies", but whose action is caused by certain sources of potential emergencies and affects the performance of the hardware, are revealed. A matrix of the nature of the effects and manifestations of the damaging factors of natural emergencies has been developed. Based on the Classifier of Emergency Situations of Ukraine, a Register of natural threats to the telecommunication network hardware has been built. New sources of threats have been discovered (13 items). The global warming process has amplified the harmful effects of known dangers and identified a number of new ones that are proposed to be classified. The “catalyst” of dangers can be anthropogenic impact, which is distinguished by the promotion of climate change, the artificial modification of the environment. The variability of the environment does not allow to present a complete list of detailed systematized threats, actions and manifestations of damaging factors and their compliance with certain threats. The list of known protective actions includes organizational measures and countermeasures. According to existing experience, the network hardware resources must comply with the principle of redundancy, in which the operational reconfiguration is performed. It is proposed to apply redundancy of communication lines by means of three-level multiplexing with mutually independent levels